أحكام الرضاع المحرم في الفقه الإسلامي: دراسة فقهية حديثية: The Ruling of Milk Kinship in Islamic Jurisprudence: Study in Legal and Prophetic Tradition - Shamsu, Lilly Suzana; Soleh Muhammad Mhanna, Jihad (‘Abqari Journal, 2020)
تهدف هذه الدارسة إلى محاولة تسليط الضوء على أحكام الرضاع المحرم في الفقه الإسلامي، لجهل الكثير من المسلمين أحكامه، فينشأ بسببه المشاكل الاجتماعية من فسخ النكاح، وانتهاك الأعراض، متبعاً ومستعينًا بالمنهج الاستقرائي التحليلي، حيث تطرقت الدراسة إلى بعض المفاهيم المتعلقة بأحكام الرضاع المحرم، بالإضافة إلى بعض الأحكام المتعلقة بالرضاع كالسن والمقدار، وقد خلص البحث إلى أن إرضاع المرأة طفلاً بالشروط المعتبرة شرعًا كان ولدها في تحريم النكاح، وللرضاع حكمتين من التحريم به فالأولى: أخلاقية والثانية: علمية. This study aims to shed light on Islamic ruling on kinship by milk (al-Ridha‘a) as well as to educate Muslims on its implication. It is very important to adhere the Islamic Law on this matter as unawareness may lead to social problems, impediment to marriage or separation of husband and wife. This study is conducted by using inductive approach that will analyze the textual content in any related documents. This study presents some concepts related to Islamic ruling on forbidden marriage due kinship by milk, the duration of breastfeeding and the amount or number of milk that to be breast fed. The study conclude that when a woman breast feeds a child (not her own) the child becomes her close relative (Mahram) provided the breastfeeding has fulfilled all the concerned Shari‘ah Law. Furthermore, the study also stated that there are moral and scientific wisdom behind the Islamic Law on this matter. On the issue pertaining the establishment of Milk Bank, the study found that is permissible for babies to consume the milk processed by the Milk Bank. Anyhow, it must fulfill all conditions that has been set by the authority.